Manajemen Operasional Pelayanan untuk Mengurangi Waktu Tunggu di Angke Heritage Restoran PIK 2 - Nabil Hamdi; Tubagus Muhammad Arif; Iham Ramadhan; Muhamad Aji Prakoso (Asosiasi Riset Ilmu Manajemen dan Bisnis Indonesia, 2025)
Angke Heritage Restaurant is a renowned traditional dining establishment that faces challenges in managing customer wait times as part of its service quality. Prolonged wait times can negatively impact customer satisfaction and reduce loyalty. This study aims to analyze the operational service management implemented at Angke Heritage Restaurant and identify strategies to reduce customer wait times. The research employs a mixed-methods approach, with data collected through direct observations, employee interviews, and customer surveys. The data is analyzed using service blueprints to identify service process stages that require improvement. The findings reveal that the longest wait times occur during the ordering and food preparation stages, primarily due to a lack of staff coordination and suboptimal management systems. Recommended strategies include implementing an online reservation system, providing employee training to enhance work efficiency, and optimizing kitchen processes through Point of Sale (POS) technology. These strategies are projected to reduce wait times by up to 30% and significantly enhance customer satisfaction. This study contributes to the literature on operational service management in restaurants and offers practical guidance for traditional restaurant managers seeking to improve service quality.